ANALYSIS METHOD OF TACTICAL PROPERTIES OF TERRAIN FOR MILITARY-ORIENTED GIS - Хірх-Ялан, в. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article considers the possibility of geoinformation analysis conduct of terrain tactical properties according to materials of digital terrain map produced by Topographic Service of the Armed Forces OF Ukraine. The author considers the method of problem solution for optimization of deployment of military units using hierarchy analysis method for processing of geospatial information and geoinformational technologies. Keywords: geoinformation support, area analysis, geoinformational technologies.